The Synergy Impact on Performance: Study of the Ministry of Finance’s Secondment Program - Triastie, Gitty Ajeng; Sampurna, Agung Firman (Interdisciplinary Social Studies, 2023)
Background: KMK 667/KM.01/2022 states that there are several areas for improvement in current conditions, such as government financial data that needs to be integrated and the absence of a single platform that provides comprehensive information and profiles of taxpayers/service users/payers. Some of these shortcomings may have a negative impact. Aim: This study aimed to analyze the impact of synergy on performance in the Ministry of Finance’s secondment program. Method: This study uses a positivism approach because it used theory as a starting point for research. The researcher’s position was outside the theory and the research object. The data and information collected were tested to confirm the research hypotheses. Literature studies were carried out by collecting and studying literature related to the themes and objects studied, such as books, journals, other research, articles, laws and regulations, official reports, and other supporting documents. The population in this study was 56 secondment teams scattered all around Indonesia in 2022, assessed by the monitoring and evaluation team and a census technique to have an accurate conclusion because all population members were included as the sample. Findings: The analysis resulted in the conclusion that synergy positively affects performance in the Ministry of Finance's secondment program. Good cooperation, feelings of mutual openness and mutual trust emerged among the participants of the secondment program because there was a common perception of a goal that needed to be achieved together.